A Delphi consultation to assess indicators of readiness to provide quality health facility-based lymphoedema management services - Walsh, Victoria L.; Fox, LeAnne M.; Brady, Molly; King, Jonathan; Worrell, Caitlin M. (PLOS Neglected Tropical Diseases, 2018)
Author summary Prior to this assessment, there was a need for clearly defined, measurable indicators for global lymphoedema management programmes to use to evaluate their lymphoedema morbidity management and disability prevention services. The results presented in this report outline a framework for indicators to assess healthcare facility-based readiness to provide quality lymphoedema management services. We describe our use of the Delphi methodology to obtain consensus on programme evaluation metrics as a model for elimination or control metrics and targets. The quality indicators developed from this Delphi consultation will be used to improve the direct inspection protocol tool that can be used to assess health facility readiness to provide quality lymphoedema management services LF endemic countries.